Phytochemical Constituents and the Effect of Processing on Antioxidant Properties of Seeds of an Underutilized Wild Legume Bauhinia Petersiana. Issue 3 (20th November 2015) - Chidewe, Cathrine Katayi; Chirukamare, Pride; Nyanga, Loveness Kuziva; Zvidzai, Cuthbert Johnson; Chitindingu, Kudakwashe
Abstract: Phytochemical constituents and effect of processing on antioxidant activity of the seeds of B auhinia petersiana were investigated. Phytochemical screening of raw seeds was done on ethanol, methanol and aqueous extracts. Antioxidant properties of methanolic extracts of the raw and processed seeds were determined using in vitro tests involving inhibition of DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl), hydrogen peroxide, superoxide anions and ferric reducing antioxidant power. Alkaloids, tannins, saponins, flavonoids, cardenolides, proteins, terpenoids, carbohydrates and anthraquinones were variedly distributed in different extracts of the seeds. The raw, boiled and roasted seeds contained similar amounts of total phenolics and tannins, however, flavonoids were higher in the roasted seeds. The DPPH radical scavenging activity of raw and processed seeds was similar to that of ascorbic acid, catechin and butylated hydroxyanisole. Reducing power increased when samples were roasted. Superoxide and H2 O2 scavenging activity of raw and processed seeds were similar to that of ascorbic acid. Practical Applications: The ground roasted seeds of B auhinia petersiana have, since time immemorial, been used as a coffee substitute by communities in Zimbabwe. Our research findings indicate that roasting of the seeds of B . petersiana resulted in increased antioxidant potential through in vitro model. These results mean that the seeds of B . petersiana could be a useful source of natural antioxidant if utilized as roasted ground coffee, compared to the raw or boiled seeds. The analyzed seeds also contained a range of phytochemicals including terpenoids, anthraquinones, cardiac glycosides, amino acids, saponins, alkaloids and phenolic compounds; hence, it would be a useful natural source of various phytochemicals that have health benefits. These research findings would be useful in promoting commercial production of coffee or other products from the wild coffee bean.